Effects of terbuthylazine on early life stages of common carp - Velisek, Josef; Stara, Alzbeta; Koutnik, Dalibor; Zuskova, Eliska (Neuro endocrinology letters, 2015)
OBJECTIVES: The aim of this study was to assess the toxicity of terbuthylazine in different developmental stages of common carp (Cyprinus carpio) on the basis of mortality, early ontogeny, occurrence of morphological anomalies, growth rate, and Fulton's condition factor during and at the conclusion of the test. DESIGN: The toxicity tests were performed on carp according to OECD 210 methodology. The developmental stages of carp were exposed to terbuthylazine at four concentrations, 2.9 (reported environmental concentration in Czech rivers); 70; 1,400; and 3,500 µg.L(-1) for 35 days and compared to carps in a non-treated control group. RESULTS: Terbuthylazine in concentration 1,400 and 3,000 µg.L(-1) caused significant (p<0.01) decrease of mass, total length and delayed in development of carp. Fish exposed to terbuthylazine showed alteration of tubular system of caudal kidney. On the basis of histopathological changes the values of LOEC=2.9 µg.L(-1) terbuthylazine were estimated. CONCLUSIONS: Chronic terbuthylazine exposure of early-life stages of common carp affected their growth rate, early ontogeny and histology. Some of the changes were observed only at higher exposures, but change founded in caudal kidney was affected in fish exposed to the real environmental concentration tested (i.e., 2.9 µg.L(-1)).
Keywords: Carps; chemické látky znečišťující vodu; Embryo, Nonmammalian; Pesticides; zygota; Triazines; Kidney; Water Pollutants, Chemical; Zygote; kapři; pesticidy; testy chronické toxicity; embryo nesavčí; Animals; triaziny; ledviny; zvířata; Toxicity Tests, Chronic